Espacio y fe en la Amazonía peruana. Sociedades religiosas y modelos de organización espacial - Novoa Goicochea, Zaniel (Pontificia Universidad Católica del Perú, 2024)
The article presents the links between Geography and Religion based on the following hypothesis religious practices of human groups participate in the construction of the space and the generation of spatial organization models in the Peruvian Amazone. The research aims to study the forms of territorial occupation and the models of space organization that emerged from religious practices. After, a theoretical framework is developed on spatial organization with emphasis on social and cultural factors. In this research, the author also proceeds to put into practice a descriptive methodological process, supported by a long field work, interviews, literature review, creation of cartography and chorematic schemes. All of these contributes to present the socio-religious structures and models of organization that correspond to the three cases of churches studied. The main contributions lead us to conclude and confirm that there is a link between geography and religion. The research let us acknowledge the relationships between society and territory are linked with practices based on the exercise of faith. Furthermore, this research allows us to understand the postulates and key concepts in the Geography of Religion such as: socio-cultural factors, socio-religious structures, religious landscapes, space organization models and others.

Este artículo presenta las relaciones entre geografía y religión basado en la hipótesis de que las prácticas religiosas de los colectivos humanos participan en la construcción del espacio y en la generación de modelos de organización espacial en la Amazonía peruana. El objetivo del presente estudio es describir las formas de ocupación del territorio y los modelos de organización del espacio que surgen a partir de dichas prácticas. Se desarrolla una aproximación teórica sobre la organización espacial con énfasis en los factores sociales y culturales, y se pone en práctica un proceso metodológico descriptivo apoyado en un amplio trabajo de campo, entrevistas, revisión bibliográfica, elaboración de cartografía y esquemas coremáticos. Todo esto contribuye a presentar las estructuras sociorreligiosas y los modelos de organización que corresponden a los tres casos de iglesias estudiadas. Los principales aportes se sintetizan en la confirmación de la relación entre geografía y religión, la comprensión de las vínculos entre la sociedad y el territorio ligadas con prácticas que se basan en el ejercicio de la fe, y la comprensión de los siguientes postulados y conceptos de la geografía de la religión: factores socioculturales estructuras sociorreligiosas, paisajes religiosos, modelos de organización del espacio y otros.
Space and faith in the Peruvian Amazon. Religious societies and models of spatial organisation
Keywords: Religions; Amazone; Religious Practices; Agro-religious Structures; Models of Spatial Organization; Coremes; Religiones; Amazonía; Prácticas religiosas; Estructuras agrorreligiosas; Modelos de organización espacial; Coremas; https://purl.org/pe-repo/ocde/ford#5.07.00